2012
DOI: 10.1038/srep00515
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analyses reveal novel strategies in HPV11,-16 and -45 early infection

Abstract: The interaction between human papillomavirus (HPV) and host cells is not well understood. We investigate the early stage of HPV infections by global expression profiling in a cell model, in which HaCaT cells were transfected with HPV11, HPV16 or HPV45 genomes. We report the differential expression of genes not previously implicated in HPV biology, such as the PSG family and ANKRD1, and of genes implicated in the biology of other viruses, e.g. MX1, IFI44 and DDX60. Carcinogenesis-related genes, e.g. ABL2, MGLL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…On a larger scale, several recent AP-MS studies have examined global host-virus protein interactions, generating comprehensive interaction networks that further highlight the benefit of applying proteomic approaches to investigating viral infection [120,124,125,129]. Moreover, the resulting large-scale protein interaction networks are useful in the development and optimization of statistical methods for characterizing protein associations, including the SAINT algorithm for determining specificity of protein interactions [130].…”
Section: Perspective: “Omic” Approaches In Characterizing Hdac Funmentioning
confidence: 99%
“…On a larger scale, several recent AP-MS studies have examined global host-virus protein interactions, generating comprehensive interaction networks that further highlight the benefit of applying proteomic approaches to investigating viral infection [120,124,125,129]. Moreover, the resulting large-scale protein interaction networks are useful in the development and optimization of statistical methods for characterizing protein associations, including the SAINT algorithm for determining specificity of protein interactions [130].…”
Section: Perspective: “Omic” Approaches In Characterizing Hdac Funmentioning
confidence: 99%
“…IFI44 is differentially expressed in rhinovirus (RV) infected primary bronchial epithelial cells derived from humans with asthma vs. normal subjects [13]. Early stage human papillomavirus (HPV) infections also induce IFI44 expression in a human keratinocyte line [14], seemingly through the expression of HPV E7 oncoprotein [15]. However, HIV-1 infection seems to down-regulate expression of a set of ISGs in primary macrophages, including IFI44 [16].…”
Section: Introductionmentioning
confidence: 99%
“…Other transcripts were potentiated by E6/E7 expression such as Cox-1 [27] . In a more recent study, E7 expression modified IFI44 , IFI44L and TP53INP2 - transcripts, which were also found to be downregulated in HPV16-positive HaCaT cells [28, 29]. The annotation of all genes discussed in the manuscript is included as Supplementary Table .…”
Section: Mrna Profilingmentioning
confidence: 99%
“…The most recent study where the HPV16 genome was transfected into HaCaT cells identified 338 differentially expressed genes (fold change between -3.8 and 3.5). The most upregulated genes were ANKRD1 , PSG s and HSPB8 and among the most downregulated genes were MMP s, SERPINB3 and SERPINB 4 [2, 29] (Fig. 1 ).…”
Section: Mrna Profilingmentioning
confidence: 99%